2020
DOI: 10.3390/nu12113454
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Lipid Composition in the Sensory Attributes and Acceptability of the Salted and Dried Mullet Roes (Bottarga): A Study in Human and Animal Models

Abstract: A taste component is implicated in the oro-sensory detection of dietary lipids and free fatty acids seem to be involved in fatty food recognition. Bottarga, the salted and semi-dried ovary product of mullet (Mugil spp.), is a rich-fat food. A comparative sensory assessment of different commercial bottarga samples was performed in insect and human models in relation to their lipid composition. The bottarga attractant effect to Ceratitis capitata was assessed by behavioral tests. The subjective odor and taste pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(42 citation statements)
references
References 47 publications
(161 reference statements)
1
41
0
Order By: Relevance
“…More specifically, because of the importance of pleasantness in food consumption, research should explore the role of food composition in sensory attributes evaluation. As a precursor, the work of Rosa et al (2020) showed that women exhibited a greater ability than men to detect pleasantness of an odor rich in free fatty acid such as the mullet roes.…”
Section: Sex Differences In Healthy Populations: Non-specific Odorsmentioning
confidence: 99%
“…More specifically, because of the importance of pleasantness in food consumption, research should explore the role of food composition in sensory attributes evaluation. As a precursor, the work of Rosa et al (2020) showed that women exhibited a greater ability than men to detect pleasantness of an odor rich in free fatty acid such as the mullet roes.…”
Section: Sex Differences In Healthy Populations: Non-specific Odorsmentioning
confidence: 99%
“…Ingredients reported in the labels were: mullet roes and salt. Three commercial samples of grated bottarga (in 70 g jars), different for the provenance of raw roes, Mugil species, and manufacturing procedures (Rosa et al, 2020), were mixed in order to obtain an adequate amount of bottarga and a representative, uniform sample of this food product for olfactory and gustatory assessment. The chemical composition (fat %, protein %, and salt %) of the grated bottarga sample used in this study was determined as mean ± standard deviation (SD) of values indicated in the respective labels of mixed commercial products (Table 1).…”
Section: Food Productmentioning
confidence: 99%
“…(2/1, v/v) solution for 1 h at room temperature in the dark (Rosa et al, 2016(Rosa et al, , 2020. After the addition of 4 ml H 2 O and centrifugation at 900Âg for 1 h, the lower chloroform phase (total lipid extract) was separated.…”
Section: Analysis Of Fatty Acid Composition In Bottarga Samplementioning
confidence: 99%
See 2 more Smart Citations